The paradoxes of empowerment: gendering NREGA in the rural landscape of India. Issue 1 (2nd January 2016) - Maiorano, Diego; Thapar-Björkert, Suruchi; Blomkvist, Hans
ABSTRACT: The growing importance of public works programmes (PWPs) as a social protection tool has attracted significant scholarly attention. However, despite the fact that the empowerment of marginalised communities is one of the key objectives of most PWPs, scant attention has been dedicated to this crucial issue. We contextualise these concerns in relation to India's Mahatma Gandhi National Rural Employment Guarantee Act (NREGA). In particular, we propose two areas which are relatively unexplored. First, the methodologies currently used to research NREGA and PWP, more generally, need to be broadened. Second, the processes that lead to empowerment need to be researched empirically.